2012
DOI: 10.1007/s00540-012-1525-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alcohol ablation with repeated thermal radiofrequency ablation in medial branch neurotomy for the treatment of recurrent thoracolumbar facet joint pain

Abstract: In our patient cohort, alcohol ablation in medial branch neurotomy provided a longer period of pain relief and better quality of life than repeated radiofrequency medial branch neurotomy in the treatment of recurrent thoracolumbar facet joint pain syndrome after successful thermal RFA without significant complications during the 24-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…The results are equivalent or even superior to previous non-controlled studies with monopolar RF, which have reported success rates between 40% and 80% [12][13][14]. A randomised, controlled study comparing monopolar RF neurotomy to alcohol ablations, reported an average effective period of 10, 7 months for the RF group, while the duration of 50% pain relief was not described [7].…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The results are equivalent or even superior to previous non-controlled studies with monopolar RF, which have reported success rates between 40% and 80% [12][13][14]. A randomised, controlled study comparing monopolar RF neurotomy to alcohol ablations, reported an average effective period of 10, 7 months for the RF group, while the duration of 50% pain relief was not described [7].…”
supporting
confidence: 51%
“…Although the Spine Intervention Society (SIS) has developed detailed guidelines for medial branch blocks and RF neurotomy, they so far only include RF interventions at the cervical and lumbar levels [5]. The clinical evidence of thermal RF neurotomy to thoracic medial branches is still limited, rated to level III [6], based on one single, randomised, controlled trial [7].…”
mentioning
confidence: 99%
“…Assessment of function in studies of chronic low back pain is vital given that this condition is the leading causes of disability and work absenteeism in the U. S. [ 1 , 2 ]. The finding of functional improvement in a large proportion of this cohort (58%) is particularly notable given the mixed results and shorter duration of follow-up of functional outcome measurement in prior studies [ 9 11 , 14 , 16 18 ].…”
Section: Discussionmentioning
confidence: 80%
“…There is a concurrent improvement in function with pain reduction (MSQ III score) [40] with variations in analgesic usage with radiofrequency ablation [35]. Some studies had a shorter duration of follow up [36]. Cohen, et al in a case-control study showed that medial branch blocks had better outcomes with radiofrequency ablation compared with IA blocks when used as a test before denervation [19].…”
Section: Technical Challengementioning
confidence: 99%
“…Radiofrequency denervation has shown to improve function, pain and analgesic use for 6-12 months [36]. Other studies have documented follow up of up to 3 years [37].…”
Section: One Block Vs Two Blocks Before Denervationmentioning
confidence: 99%